2014
DOI: 10.1111/jpc.12620
|View full text |Cite
|
Sign up to set email alerts
|

Are vitamin D levels affected by acute bacterial infections in children?

Abstract: In children, 25OHD levels are not affected by acute bacterial infections; 25OHD levels taken during acute bacterial infection are representative of baseline levels. 25OHD levels collected during acute bacterial infection provide reliable information for case-control studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
1
4
0
1
Order By: Relevance
“…When adjusting for age there also was no significant difference between plasma-25(OH)D measured during pneumonia and after recovery. The finding of similar 25(OH)D concentrations in baseline and recovery samples is consistent with the study of 30 children with bacterial infections [ 18 ], where no differences was found during acute illness compared to four weeks after the infection.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…When adjusting for age there also was no significant difference between plasma-25(OH)D measured during pneumonia and after recovery. The finding of similar 25(OH)D concentrations in baseline and recovery samples is consistent with the study of 30 children with bacterial infections [ 18 ], where no differences was found during acute illness compared to four weeks after the infection.…”
Section: Discussionsupporting
confidence: 89%
“…Recently, the authors of a systematic review concluded that vitamin D status measured during the acute phase should be interpreted with care [ 16 ], but most of the studies included in this systematic review were in non-infectious patients, except for one study including 14 adult patients with malaria, in whom no change in 25(OH)D was found between the acute phase and a follow-up 2–6 weeks later [ 17 ]. In another recent study of 30 children aged between nine months and 16 years with bacterial illnesses, four of whom had pneumonia, no significant difference was found in the 25(OH)D concentration during the illness compared to after one month [ 18 ]. We are not aware of similar studies in younger children with acute lower respiratory tract infection (ALRI).…”
Section: Introductionmentioning
confidence: 99%
“…However, a study of children by Binfield et al. demonstrated that vitamin D levels were not affected by the presence of acute bacterial infections. Having received a fluid bolus was associated with lower vitamin D level than no fluid bolus in our cohort, and this finding was similar to other studies .…”
Section: Discussionmentioning
confidence: 99%
“…However, low baseline 25(OH)D levels reflect reduced UVB exposure and dietary vitamin D over a prolonged period of weeks . A recent study found that acute bacterial infection has little effect on baseline 25(OH)D levels in children . These studies suggest that acute illness and infection may not influence 25(OH)D levels.…”
Section: Discussionmentioning
confidence: 99%